ANALOGUE SAUSAGE FORMULATION OF TEMPEH-WHITE OYSTER MUSHROOMS (PLEUROTUS OSTREATUS) WITH THE ADDITION OF CARRAGEENAN - Septi Rohmawati; Akhmad Mustofa; Yannie Asrie Widanti (University of Sultan Ageng Tirtayasa, 2019)
Sausage is a food product that is processed as a variety of food. Tempeh and white oyster mushroom (Pleurotus ostreatus) contain many nutrients needed by the body. In addition, carrageenan also contributes to the nutritional content of the product. This research was conducted to determine the chemical and sensory characteristics of sausage that are rich in fiber and received by consumers. This study used completely randomized design method (CRD) which consists of two factors. The first factor was the substitution of tempeh and white oyster mushroom with a ratio of 50:100; 75:75; 100:50. The second factor was the addition of carrageenan, including 4, 6 and 8 g. The chosen formulation was on the treatment of a comparison of 75 g of tempehh and 75 g of white oyster mushroom with the addition 6 g of carrageenan. The chemical properties of the analogue sausage was:14% of protein, 11.22% of fat, 44.24% of moisture, 6.02% of crude fiber, 2.37% of ash and 27.29% of total cabohydrate. While for sensory test color was 2.96, flavour tempeh 2.45, flavour of mushroom 1.74, texture of 2.55 and overall preference 2.45.